Respostas

2014-06-23T14:08:13-03:00
F(8) = 1 - 5*8
f(8) = 1 - 40
f(8) = - 39

f(10) = 1 - 5*10
f(10) = 1 - 50
f(10) = - 49

f(12) = 1 - 5*12
f(12) = 1 - 60
f(12) = - 59

1 5 1
2014-06-23T14:26:27-03:00
QUANDO APARECER ESSE TIPO DE QUESTÃO É SÓ VC TROCAR O "x" PELO VALOR QUE ESTÁ NO PARENTESE.
DADA A FUNÇÃO:  f (X) = 1-5 X 
E) F(8) 
  f (X) = 1-5 X 
 f (8) = 1-5 *8
 f (8) = 1-40
 f (8) = -39

 
F) F(10)
 f (X) = 1-5 X 
 f (10) = 1-5*10
 f (10) = 1-50
 f (10) = -49

G)F(12)
 f (X) = 1-5 X 
 f (12) = 1-5*12
 f (12) = 1-60
 f (12) = -59 
 
1 5 1